Management information systems: managing the digital firm - Laudon, Kenneth C; Laudon, Jane P. (Delhi : Pearson Education, 2007)
Business
Keywords: Management information systems; Information technology; Digital firm; Internet business; Business Information Systems; Information Systems; Digital Age; E-commerce; Knowledge Management; Managing global systems